2011
DOI: 10.1080/09540121.2011.608419
|View full text |Cite
|
Sign up to set email alerts
|

The association of hospital, clinic and provider volume with HIV/AIDS care and mortality: systematic review and meta-analysis

Abstract: The objective of this systematic review and meta-analysis is to examine the association between hospital, clinic and provider patient volumes on HIV/AIDS patient outcomes including mortality, antiretroviral (ARV) use and proportion of patients on indicated opportunistic infection (OI) prophylaxis. We searched MEDLINE and nine other electronic databases from 1 January 1980 through 29 May 2009. Experimental and controlled observational studies of persons with HIV/AIDS were included. Studies examined the volume o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
13
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 28 publications
6
13
1
Order By: Relevance
“…Consistent with previous reviews with a similar focus (Handford, Rackal, Tynan, Rzeznikiewiz, & Glazier, 2012;Rackal et al, 2011), we found positive associations between health-care provider expertise and health outcomes among HIV-infected patients. However, our results regarding facility volume were less convincing than those in previously published reviews (Handford et al, 2012;Handford, Tynan, Rackal, & Glazier, 2006).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Consistent with previous reviews with a similar focus (Handford, Rackal, Tynan, Rzeznikiewiz, & Glazier, 2012;Rackal et al, 2011), we found positive associations between health-care provider expertise and health outcomes among HIV-infected patients. However, our results regarding facility volume were less convincing than those in previously published reviews (Handford et al, 2012;Handford, Tynan, Rackal, & Glazier, 2006).…”
Section: Discussionsupporting
confidence: 80%
“…However, our results regarding facility volume were less convincing than those in previously published reviews (Handford et al, 2012;Handford, Tynan, Rackal, & Glazier, 2006). These reviews differ in the sense that they included many studies that took place before the introduction of cART.…”
Section: Discussioncontrasting
confidence: 56%
“…With regards to health facility level factors, evidence suggests that hospital volume and provider training and experience improve outcomes in HIV-infected patients [20,21]. However, professionals involved in designing best practices for HIV outpatient care are largely dependent on results from studies predating the advent of cART, often performed in an inpatient setting.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are consistent with those of a previous systematic review demonstrating that physician HIV experience is specifically associated with improved HIV-specific outcomes, such as adherence to ART prescribing. 2 Another review conducted by the same authors 3 attempted to distinguish physician training from physician HIV experience, and mainly concluded that both are important for HIV-specific outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that clinicians with more HIV training, HIV experience, or both provide higher quality of care as measured by disease-specific indicators, including ART prescribing. [1][2][3][4][5][6] Many of these studies, however, were performed early in the ART era, when both disease and treatments were novel and complex. Recent work has found similar quality of HIV-specific care between generalist and specialist physicians, even though the HIV experience of these physicians varied.…”
Section: Introductionmentioning
confidence: 99%